Non-disease Specific Health Promotion Interventions for Chronically Ill Adolescents in Medical Settings: A Systematic Review - Isabelle Aujoulat; Sophie Dechêne; Magali Lahaye (Frontiers Media S.A., 2018)
Adolescents with chronic conditions are highly likely to encounter physical, social and psychological difficulties that can threaten their overall wellbeing and health. As any other adolescent, they need to be helped to tackle the non-medical determinants of their health. This is the aim of primary prevention and general health promotion interventions. The present paper aims to review any hospital-based intervention that strives to promote general health in chronically ill teenagers. A systematic process of search and screening revealed four articles that presented and evaluated non-disease specific interventions that explicitly aimed to promote the overall health of chronically ill teenagers in clinical settings. Congruently with health promotion principles and values, the interventions described in our selection of articles targeted positive health determinants, in terms of personal skills and attitudes that contribute to psychosocial resiliency. The clinical relevance and feasibility of developing non-disease specific health promotion interventions in clinical settings was confirmed. However, the lack of relevant reported details did not allow us to highlight the key factors and mechanisms associated with successful interventions for health promotion targeted at chronically ill adolescents attending health care settings. Moreover, the design of the included studies varied in quality: number of participants, presence of a post-test and a follow-up, use of validated questionnaires, etc. Well-conducted non-disease specific clinical health promotion interventions still remain an under-investigated area of research, and maybe even of practice.